n Persoonlikheidsondersoek van 'n groep inrigtingversorgde ongehude moeders - Odendal, F. J.(Francois Johannes),1954- (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M.A.) -- Universiteit van Stellenbosch, 1980.